2011
DOI: 10.2215/cjn.09421010
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Rituximab in Children with Steroid- and Calcineurin-Dependent Nephrotic Syndrome

Abstract: SummaryBackground and objectives Prednisone and calcineurin inhibitors are the mainstay therapy of idiopathic nephrotic syndrome (INS) in children. However, drug dependence and toxicity associated with protracted use are common. Case series suggest that the anti-CD20 monoclonal antibody rituximab (RTX) may maintain disease remission. Design, setting, participants, & measurementsThis open-label randomized controlled trial was powered to show that a strategy based on RTX and lower doses of prednisone and calcine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
148
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(161 citation statements)
references
References 37 publications
11
148
0
1
Order By: Relevance
“…RTX has been used with some success in children with steroid-dependent idiopathic nephrotic syndrome, as shown in several case reports [81], [82], [83] and [84]. A randomized clinical trial of 54 children with steroid-and calcineurin inhibitordependent nephrotic syndrome treated with RTX versus standard therapy showed that proteinuria decreased by 70% more in the RTX arm [85]. Importantly, 63% of patients treated with RTX were drug-free at 3 months versus 3.7% in the control arm.…”
Section: Focal Segmental Glomerulosclerosis and Minimal Change Diseasementioning
confidence: 96%
“…RTX has been used with some success in children with steroid-dependent idiopathic nephrotic syndrome, as shown in several case reports [81], [82], [83] and [84]. A randomized clinical trial of 54 children with steroid-and calcineurin inhibitordependent nephrotic syndrome treated with RTX versus standard therapy showed that proteinuria decreased by 70% more in the RTX arm [85]. Importantly, 63% of patients treated with RTX were drug-free at 3 months versus 3.7% in the control arm.…”
Section: Focal Segmental Glomerulosclerosis and Minimal Change Diseasementioning
confidence: 96%
“…Between 2011 and 2015, five clinical trials on the use of rituximab in idiopathic nephrotic syndrome were reported: four as journal articles (27)(28)(29)(30) and one in abstract form. Results of four prospective studies were also published in the same period (see below) (27,31,32).…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%
“…Tables 2 and 3 summarize the key characteristics and findings from these randomized controlled trials. One trial enrolled children with idiopathic nephrotic syndrome maintained in remission with high-dose steroids alone (27), three trials enrolled children maintained in remission with steroids and calcineurin inhibitors (28,29), and one trial assessed the effect of rituximab in children with nephrotic syndrome resistant to both steroids and calcineurin inhibitors (30). Figure 2 presents a flow chart of treatment of idiopathic nephrotic syndrome based on randomized controlled trials.…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A randomized controlled study by Ravani et al 19 has also shown noninferiority of rituximab therapy in children with nephrotic syndrome who were resistant to only steroid therapy but dependent on both steroids and CNIs. In this trial, 27 patients were randomized to receive one to two doses of rituximab followed by withdrawal of prednisone and CNIs over 6 weeks, whereas 27 patients continued standard therapy with prednisone and CNIs.…”
Section: Disclosuresmentioning
confidence: 97%